Impact of weight loss on ankle‐brachial index and interartery blood pressures. (24th February 2014) - Espeland, Mark A.; Lewis, Cora E.; Bahnson, Judy; Knowler, William C.; Regensteiner, Judith G.; Gaussoin, Sarah A.; Beavers, Daniel; Johnson, Karen C.; ,; Brancati, Frederick L.; Swartz, Lee; Cheskin, Lawrence; et al.
<x xml:space="preserve">Abstract</x> Objective To assess whether weight loss improves markers of peripheral artery disease and vascular stenosis. Methods The Action for Health in Diabetes randomized clinical trial compared intensive lifestyle intervention (ILI) for weight loss to a control condition of diabetes support and education (DSE) in overweight or obese adults with type 2 diabetes. Annual ankle and brachial blood pressures over four years were used to compute ankle‐brachial indices (ABIs) and to assess interartery blood pressure differences in 5018 participants. Results ILI, compared to DSE, produced 7.8% (Year 1) to 3.6% (Year 4) greater weight losses. These did not affect prevalence of low (<0.90) ABI (3.60% in DSE versus 3.14% in ILI; P = 0.20) or elevated (>1.40) ABI (7.52% in DSE versus 7.59% in ILI: P = 0.90), but produced smaller mean (SE) maximum interartery systolic blood pressure differences among ankle sites [19.7 (0.2) mmHg for ILI versus 20.6 (0.2) mmHg for DSE (P < 0.001)] and between arms [5.8 (0.1) mmHg for ILI versus 6.1 (0.1) mmHg for DSE (P = 0.01)]. Conclusions Four years of intensive behavioral weight loss intervention did not significantly alter prevalence of abnormal ABI, however, it did reduce differences in systolic blood pressures among arterial sites.